2021
DOI: 10.1021/acs.energyfuels.1c02125
|View full text |Cite
|
Sign up to set email alerts
|

Iron/Iron Carbide (Fe/Fe3C) Encapsulated in S, N Codoped Graphitic Carbon as a Robust HER Electrocatalyst

Abstract: In the present work, iron carbide (Fe/Fe3C) encapsulated in sulfur and nitrogen codoped graphitic carbon was synthesized using a low-cost, one-step pyrolytic method. The as-prepared nanomaterials were investigated for catalytic hydrogen evolution reaction (HER) in acidic medium. Doping of sulfur and nitrogen was achieved by adding different weights of thiourea along with ferrocene and toluene precursors. X-ray photoelectron spectroscopy and energy-dispersive X-ray spectroscopy verify the presence of sulfur and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Pyridine-N and pyrrole-N with a planar structure can enhance the conductivity of the carbon matrix, which is advantageous to electrocatalytic performance . The existence of Mo–N indicated the doping of N into Mo 2 C lattices. , In the P 2p profile of the SKF-derived carbon matrix (Figure c), the peak of 133.0 eV corresponded to P–C species, and the one at 133.9 eV was ascribed to P–O resulting from surface oxidation. , In Mo 2 C@NPC, two new peaks (129.5 and 130.4 eV) were observed, associated with 2p 3/2 and 2p 1/2 of the P–Mo species, respectively, which confirmed P-doping into Mo 2 C. Regarding the absence of Mo 2 N and MoP phases in the XRD pattern (Figure a), we can assume that the surface of Mo 2 C serves as HER active sites with the optimized electronic configurations due to N, P co-doping . Also, the P–O species on the surface can facilitate the HER process because the P site usually acts as a proton-acceptor center during electrocatalysis …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pyridine-N and pyrrole-N with a planar structure can enhance the conductivity of the carbon matrix, which is advantageous to electrocatalytic performance . The existence of Mo–N indicated the doping of N into Mo 2 C lattices. , In the P 2p profile of the SKF-derived carbon matrix (Figure c), the peak of 133.0 eV corresponded to P–C species, and the one at 133.9 eV was ascribed to P–O resulting from surface oxidation. , In Mo 2 C@NPC, two new peaks (129.5 and 130.4 eV) were observed, associated with 2p 3/2 and 2p 1/2 of the P–Mo species, respectively, which confirmed P-doping into Mo 2 C. Regarding the absence of Mo 2 N and MoP phases in the XRD pattern (Figure a), we can assume that the surface of Mo 2 C serves as HER active sites with the optimized electronic configurations due to N, P co-doping . Also, the P–O species on the surface can facilitate the HER process because the P site usually acts as a proton-acceptor center during electrocatalysis …”
Section: Resultsmentioning
confidence: 97%
“…34,35 In Mo 2 C@NPC, two new peaks (129.5 and 130.4 eV) were observed, associated with 2p 3/2 and 2p 1/2 of the P−Mo species, respectively, 24 which confirmed P-doping into Mo 2 C. Regarding the absence of Mo 2 N and MoP phases in the XRD pattern (Figure 2a), we can assume that the surface of Mo 2 C serves as HER active sites with the optimized electronic configurations due to N, P co-doping. 36 Also, the P−O species on the surface can facilitate the HER process because the P site usually acts as a proton-acceptor center during electrocatalysis. 37 The nanostructure of Mo 2 C@NPC was analyzed using SEM and TEM.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Moreover, the above results also demonstrate the excellent HER electrocatalytic activity of FeMn@BNPCFs-900 in comparison with those of other transition-metal-based catalysts (as shown in Table S1). For example, in 1.0 M KOH, the E 10 value (−0.247 V vs RHE) of the optimal FeMn@BNPCFs-900 catalyst is better than most Mn-/Fe-based materials [such as Fe@C-SN (−0.52 V vs RHE), Fe@N–C/RGO (−0.39 V vs RHE), Fe/P/C 0.5 –800 (−0.256 V vs RHE), Fe 2 P (−0.30 V vs RHE), and Cu 2 O@MnO 2 NW@NS (−0.248)], which is just a little more negative than those of Mn-FeP NPs (−0.175 V vs RHE), mesoporous Mn-FeP (−0.173 V vs RHE), Fe-H 2 cat (−0.20 V vs RHE), and porous FeP nanosheets (−0.24 V vs RHE) …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the above results also demonstrate the excellent HER electrocatalytic activity of FeMn@BNPCFs-900 in comparison with those of other transition-metal-based catalysts (as shown in Table S1). For example, in 1.0 M KOH, the E 10 value (−0.247 V vs RHE) of the optimal FeMn@BNPCFs-900 catalyst is better than most Mn-/Fe-based materials [such as Fe@C-SN (−0.52 V vs RHE), 33 Fe@N−C/RGO (−0.39 V vs RHE), 34 Fe/P/C 0.5 − 800 (−0.256 V vs RHE), 32 Fe 2 P (−0.30 V vs RHE), 35 and Cu 2 O@MnO 2 NW@NS (−0.248)], 36 which is just a little more negative than those of Mn-FeP NPs (−0.175 V vs RHE), 37 mesoporous Mn-FeP (−0.173 V vs RHE), 38 Fe-H 2 cat (−0.20 V vs RHE), 39 and porous FeP nanosheets (−0.24 V vs RHE). 40 To further disclose the HER electrocatalytic kinetics of FeMn@BNPCFs-T and Pt/C catalysts, their corresponding Tafel plots (log j vs E) were calculated and are recorded in Figure 7c; the Tafel slopes are recorded as 226.94, 212.81, 127.69, 104.89, and 130.51 mV per decade (mV dec −1 ) for FeMn@BNPCFs-600, FeMn@BNPCFs-700, FeMn@ BNPCFs-800, FeMn@BNPCFs-900, and FeMn@BNPCFs-1000, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Yang et al, reported the excellent catalytic performance of a WS 2 nanosheets/reduced graphene oxide composite for HER, which was attributed to the fast charge transfer resulting from the strong interaction between the metallic species and carbon support [202]. Encapsulated Fe/Fe 3 C particles on S, N co-doped graphitic carbon also revealed promising electrocatalytic activity for HER-the incorporation of a doped-carbon support led to an increase of the number of available active sites, enhancing the Fe 3 C performance [203]. Additional examples of metal/carbon catalysts for HER can be found in the comprehensive reviews provided by Wang [204].…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%